If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 23 = 4x + 2 Reorder the terms: 23 + 3x = 4x + 2 Reorder the terms: 23 + 3x = 2 + 4x Solving 23 + 3x = 2 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 23 + 3x + -4x = 2 + 4x + -4x Combine like terms: 3x + -4x = -1x 23 + -1x = 2 + 4x + -4x Combine like terms: 4x + -4x = 0 23 + -1x = 2 + 0 23 + -1x = 2 Add '-23' to each side of the equation. 23 + -23 + -1x = 2 + -23 Combine like terms: 23 + -23 = 0 0 + -1x = 2 + -23 -1x = 2 + -23 Combine like terms: 2 + -23 = -21 -1x = -21 Divide each side by '-1'. x = 21 Simplifying x = 21
| 3x^2+39=30x | | (3-x)/4=-3 | | a*a+1+6a*a+8a=0 | | -2(c+6)=c+3+2c | | a^3+1+3a*a+3a=0 | | 5x-4y=4 | | 4r^2+32r+55=0 | | -(b-2)-2(2b+3)=1 | | x+3x+3x+2=120 | | 2y-7=-15 | | 8(254+x)+4(254-x)=254 | | -3(k-2)=-2(3k-1)+1 | | X^2+1.7x-4.8=0 | | logy+2logx=3 | | 1/4x+9=-2 | | x+x+5+2x=53 | | 2x+2.1=6.7 | | -6x+17=-79 | | 5x+48+7x=x+4 | | 2x^3=9 | | x-5/9+1-x/5 | | X+2=y-2 | | f(x)=0.01(2x) | | 1.5x=48 | | n+6+n=3m+7m-14 | | 8(381-.5y)+4y=3048 | | n=3m | | -17=x/5 | | 1/3x=11/15+2/5 | | T/3=-24 | | n=n+6 | | X/3=20 |